Distance Relationships - Holmes, Mary. author. aut Link
X, 212 p.
Keywords: Drawing on interviews with UK couples in distance relationships, this book seeks to explain, evaluate and advance sociological debates about intimate life. It provides a rich and human perspective on how bodies, emotions and connections to others are key in maintaining intimate relationships.